2014
DOI: 10.1017/s0950268814002064
|View full text |Cite
|
Sign up to set email alerts
|

Allelic variants at codon 146 in thePRNPgene show significant differences in the risk for natural scrapie in Cypriot goats

Abstract: Previous studies have shown the association between the polymorphisms serine (S) or aspartic acid (D) at codon 146 of the PRNP gene and resistance to scrapie. All goats aged >12 months (a total of 1075 animals) from four herds with the highest prevalence of scrapie in the country were culled and tested, of which 234 (21·7%) were positive by either the rapid test or immunohistochemistry (IHC) for any of the tissues tested. The odds of scrapie infection occurring in NN146 goats was 101 [95% credible interval (Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
24
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 23 publications
8
24
0
Order By: Relevance
“…The sensitivity of detection using posterior brainstem appeared to be strongly dependent on the age of tested individuals, which is consistent with the known pathogenesis of TSE. Similar data were obtained from studies of a large UK goat herd ) and four scrapie affected goat herds in Cyprus (Ortiz-Pelaez et al, 2014b). These data confirm that the age of the tested individuals (incubation stage) strongly influences the probability of being detected by surveillance.…”
Section: Factors Affecting Active Surveillance -Population Sampling Asupporting
confidence: 82%
See 1 more Smart Citation
“…The sensitivity of detection using posterior brainstem appeared to be strongly dependent on the age of tested individuals, which is consistent with the known pathogenesis of TSE. Similar data were obtained from studies of a large UK goat herd ) and four scrapie affected goat herds in Cyprus (Ortiz-Pelaez et al, 2014b). These data confirm that the age of the tested individuals (incubation stage) strongly influences the probability of being detected by surveillance.…”
Section: Factors Affecting Active Surveillance -Population Sampling Asupporting
confidence: 82%
“…However studies based on current active surveillance programmes in goats demonstrated that whatever the number of screening tests performed, post-mortem surveillance has limited success in identifying infected animals Corbiere et al, 2013b;Ortiz-Pelaez et al, 2014b). Similar findings were reported by Hopp et al (2003) when assessing the performance of TSE active surveillance in the Norwegian sheep population.…”
Section: Factors Affecting Active Surveillance -Population Sampling Asupporting
confidence: 69%
“…These variants include Met-142, 13,17,21,23 His-154, 14,18,19,21,23 Arg-143, 18 and alleles with stronger protective effects, such as Ser-146, Asp-146, 14,19,20 Gln-211 11,21,23 and Lys-222. 11,[21][22][23] These alleles' relative low occurrence frequency among herds and/or goat breeds examined in field studies, suggests that additional investigations within the context of a well defined experimental scheme, including sufficient test samples and controls, are required prior to gaining further conclusive information on their effects.…”
Section: Discussionmentioning
confidence: 99%
“…6,[9][10][11][12][13][14][15][16] Field studies, conducted in different countries on a variety of goat breeds, assigned some degree of protection against scrapie to the following alleles Met-142, Arg-143, Asp-146, Ser-146, His-154, Gln-211 and Lys-222. 11,13,14,[17][18][19][20][21][22][23] Among these, Met-142 is linked to prolonged incubation period, 13,17,21,23 while Arg-143 18 and His-154 14,18,19,21,23 are associated with moderate protection. Ser-146 or Asp-146, 14,19,20 Gln-211 11,21,23 and Lys-222 11,[21][22][23] are associated with higher degrees of protection, suggesting that they could be used as candidate alleles, targeted by a potential selective breeding strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Association between PrP genotype and natural scrapie infection risk in French goats was assessed, the statistical analyses indicated that P240 mutation had no direct impact on scrapie infection risk, H154, Q211 and K222 mutation were associated with high resistance to scrapie (Corbière et al, 2013). The epidemiological evidence for the resistance to natural scrapie at population associated with allelic variants D146 and S146 was provided in infected Cypriot goat (Ortiz-Pelaez et al, 2015).…”
Section: Role Of Prnp In Small Ruminantsmentioning
confidence: 99%